A case of cyclic neutropenia - Ghimire, Amrit; Shah, Ganesh (Journal of Patan Academy of Health Sciences, 2015)
A 14-year-old girl presented with recurrent episodes of pharyngitis, aphthous ulcers, diarrhea and fever for the past four years. The episodes lasted a week each time. The patient was admitted and blood studies revealed neutropenia. On further investigations, it was found that her neutrophil count dropped to less than 0.5 x 10⁹/L after every three weeks. Bone marrow study was normal. She was diagnosed as cyclic neutropenia.Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):46-48